Development Of Pop-Up Book Learning Media On Earth Oil Materials - Yoshiya Hazumi (International Journal of Science and Society, 2020)
The aimed of this study was to develop learning media called pop-up book of petroleum. The method was research and development (Research and Development) with the ADDIE model of which consisted of 5 steps: Analysis, Design, Development, Implementation and Evaluation. The data were collected using questionnaire for media validation. The results showed that pop-up book was found to be 92.67% valid (very decent), meant that the developed pop-up book could be study in terms of its effectiveness in learning